2016
DOI: 10.1080/14787210.2017.1250625
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and opportunities in the treatment of ventilator-associated pneumonia

Abstract: Ventilator-associated pneumonia (VAP) is a distinct clinical entity characterized by an onset after 48 hours of the application of mechanical ventilation (MV). Protocols exist to aid in the prevention of VAP, but this infection carries a devastating impact on patient morbidity and potentially mortality. Areas covered: In this review we present key concepts from existing guidelines to aid clinicians. Challenges remain in defining this disease and, most importantly appropriate empiric antimicrobial treatment is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 91 publications
0
21
0
Order By: Relevance
“…Therefore, avoidance of VAP in intubated neonates is thus significance in acute care situations must starts with avoiding or controlling time of mechanical ventilation whenever possible. [4] According to the Center for Disease Control and Prevention (CDC) and National Healthcare Safety Network, VAP is clear as a subtype of pneumonia happens up to 48 hours after beginning of mechanical ventilation in neonates who had no previous lung infections at a period of initiating mechanical ventilation as emplace on the date of occasion or the day before. Inappropriately, little studies have attentive on neonates, particularly those with a low or very low birth weight.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, avoidance of VAP in intubated neonates is thus significance in acute care situations must starts with avoiding or controlling time of mechanical ventilation whenever possible. [4] According to the Center for Disease Control and Prevention (CDC) and National Healthcare Safety Network, VAP is clear as a subtype of pneumonia happens up to 48 hours after beginning of mechanical ventilation in neonates who had no previous lung infections at a period of initiating mechanical ventilation as emplace on the date of occasion or the day before. Inappropriately, little studies have attentive on neonates, particularly those with a low or very low birth weight.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the standard diagnostic criteria for VAP as a new and persistent radiographic infiltrates on chest X ray and deteriorating gas exchange in ventilated neonates for at least 48 hours and who revealed at least 3 of the subsequent criteria: temperature instability (elevation of body temperature > 38 • C) with no other familiar cause, leukopenia 4,000/mL 3 , variation in characteristic of respiratory discharges (purulent pulmonary secretion), rise in nominal fraction of inspired oxygen to > 10%, tachycardia or bradycardia , and respiratory distress. [4,8] Evidence-based strategies for the prevention of VAP and improving the quality of care; [5,9] primarily accomplished by the 'bundle approach'. Which comprises concurrent application of numerous evidence-based preventive approaches that, when implemented together, achieve better patient outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The annual cost of care for VAP in the US is $2 billion (Terjesen et al, 2017;Zand et al, 2017). Prevention of VAP in intubated patients is thus a priority in critical care settings (Schreiber and Shorr, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The rate of VAP and the related mortality varies around the world, with the highest in developing countries. Schreiber and Shorr (2017) reported 13⋅6 cases/1000 ventilator days in the US compared to 44⋅3 cases/1000 ventilator days in Ecuador (Yepez et al, 2017). In Jordan, Samrah et al (2016) revealed VAP-related mortality at 53%.…”
Section: Introductionmentioning
confidence: 99%
“…Park (31) reported that fever contributed to pronged mechanical ventilation for critically ill patients. Moreover, prolonged endotracheal intubation may increase the risk of ventilator-associated pneumonia, indicated as a positive chest X-ray (32). Furthermore, pneumonia is a significant predictor of poor outcome among patients resuscitated from IHCA (33).…”
Section: Discussionmentioning
confidence: 99%